Metal Detector With Beat Frequency Method - Nuryadin Adil (Institute of Computer Science (IOCS), 2022)
The bomb terror that occurred in various regions is very troubling, because it causes us to feel anxious when we go anywhere. Bombs which are usually made of metal must be detected by a device called a metal detector